THE PROPERTIS OF TIDAL FORCES IN THE KERR METRIC - Rasulova, A. M. (Одеські астрономічні публікації, 2016)
The expression for the tidal forces of the two relativistic protons at a distance of the order of the Compton wavelength near a rotating black hole is found. The analysis shows that the tidal forces are dependent on the plane of incidence and sharply increase with increasing Lorentz factor.